2020
DOI: 10.1016/j.jinf.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Early administered antibiotics do not impact mortality in critically ill patients with COVID-19.

Abstract: Early administered antibiotics do not impact mortality in critically ill patients with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 4 publications
2
54
2
2
Order By: Relevance
“…Of 16,378 studies identified, after duplicate removal, we reviewed a total of 7469 studies via title and abstract screening, 523 of which were assessed via full-text screening. We included 154 studies in the final analysis ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of 16,378 studies identified, after duplicate removal, we reviewed a total of 7469 studies via title and abstract screening, 523 of which were assessed via full-text screening. We included 154 studies in the final analysis ( 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ,…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 is known to cause a sepsis syndrome [ 4 , 21–23 ]; in our cohort, 25% of patients adjudicated to not have bCAP met sepsis criteria, highlighting the complexity around antibiotic decision-making in patients with COVID-19. A previous study of COVID-19 patients admitted to the ICU failed to demonstrate a benefit of early antibiotics (ie, antibiotics given before arrival to the ICU) on mortality or development of ventilator-associated infection or bacteremia [ 24 ]. This underscores the ongoing need for more accurate ways to identify patients likely to benefit from antibiotics in lower respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…18 Additionally, early guidelines for critically ill patients with COVID-19 recommended consideration of antibiotics due to the possibility of bacterial co-infection, despite a lack of evidence demonstrating improved outcomes. 19,20 Although not directly related to COVID-19 infections, the pandemic public health response effort appears to have significantly altered patterns of ED utilization. Several reports confirm dramatic decreases in ED volumes for emergent conditions, potentially related to "stay at home" orders or fear of COVID-19 exposure in the hospital.…”
Section: Potential Adverse Effects Of Covid-19 On Emergency Departmenmentioning
confidence: 99%
“… 18 Additionally, early guidelines for critically ill patients with COVID-19 recommended consideration of antibiotics due to the possibility of bacterial co-infection, despite a lack of evidence demonstrating improved outcomes. 19 , 20 …”
Section: Potential Adverse Effects Of Covid-19 On Emergency Departmenmentioning
confidence: 99%